2010
DOI: 10.1007/s00394-010-0125-8
|View full text |Cite
|
Sign up to set email alerts
|

Immunoregulatory effects of the flavonol quercetin in vitro and in vivo

Abstract: In vitro, quercetin reduced DC adhesion and oxLDL-induced DC differentiation. In vivo, quercetin reduced circulating plasmacytoid DCs and systemic ADMA-levels. The immunoregulatory effects of quercetin may contribute to the anti-atherosclerotic potential of flavonols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 32 publications
0
35
0
1
Order By: Relevance
“…OxLDL influences maturation and motility of DCs [42,43]. In proinflammatory DCs, increased levels of LOX-1 expression were observed.…”
Section: Influence Of Lox-1 On Macrophagesmentioning
confidence: 99%
“…OxLDL influences maturation and motility of DCs [42,43]. In proinflammatory DCs, increased levels of LOX-1 expression were observed.…”
Section: Influence Of Lox-1 On Macrophagesmentioning
confidence: 99%
“…Daily supplementation with 730 mg quercetin for 28 days reduces systolic, diastolic and mean arterial pressure in subjects with stage 1 hypertension [30], as well as with 150 mg provides protection against cardiovascular disease in overweight subjects [31] and reduces niacin-induced flush in humans [32]. Recently, it is reported that male volunteers take 500 mg of quercetin twice daily over 4 weeks show immunoregulatory effects [29]. Thus, it is possible that quercetin may exert some of these activities at the tested dosages attained by consuming quercetin-containing human food.…”
Section: Quercetinmentioning
confidence: 99%
“…Quercetin or allopurinol was orally gavaged at 9: 00 a.m. on the day when oxonate was given. Dosages of quercetin were determined based on the conversions from clinical adult dosages [29][30][31][32] and our previous and preliminary studies. According to the reports in subjects, daily supplementation dosages of quercetin in subjects are 1,000 mg [29], 730 mg [30] and 150 mg [15,31], respectively.…”
Section: Animals and Drug Administrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Quercetin has been observed to counter NF-κB directly and also through its antioxidant role in neutralizing reactive oxygen species (Boots et al 2008). Additionally, quercetin has been shown to modulate the immune response, such as by suppressing dendritic cells (Huang et al 2010;Nickel et al 2011). Quercetin treatment, therefore, demonstrates the potential to counter the breakdown of the IP in AA.…”
Section: Hsp70mentioning
confidence: 99%